2018
DOI: 10.1038/s41467-018-05771-8
|View full text |Cite
|
Sign up to set email alerts
|

Galectin-9 binds IgM-BCR to regulate B cell signaling

Abstract: The galectin family of secreted lectins have emerged as important regulators of immune cell function; however, their role in B-cell responses is poorly understood. Here we identify IgM-BCR as a ligand for galectin-9. Furthermore, we show enhanced BCR microcluster formation and signaling in galectin-9-deficient B cells. Notably, treatment with exogenous recombinant galectin-9 nearly completely abolishes BCR signaling. We investigated the molecular mechanism for galectin-9-mediated inhibition of BCR signaling us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
101
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(110 citation statements)
references
References 70 publications
7
101
1
1
Order By: Relevance
“…Although Galectin-8 does not form multivalent oligomers as Galectin-3, a non-quantitative proteomic analysis of Galectin-8 binding partners in B cells revealed that Galectin-8 interacts directly with the BCR ( Table S1 ), which was also supported by a pull-down assay showing that Galectin-8 binds to the BCR. Analogously, Galectin-9 was recently shown to interact directly with the BCR and CD45 and to suppress BCR downstream signaling by restricting the lateral mobility of the receptor and favoring its association with inhibitory molecules ( Cao et al., 2018 ). In contrast to the effect of Galectin-9, we did not observe an inhibition of BCR signaling in the presence of Galectin-8.…”
Section: Discussionmentioning
confidence: 99%
“…Although Galectin-8 does not form multivalent oligomers as Galectin-3, a non-quantitative proteomic analysis of Galectin-8 binding partners in B cells revealed that Galectin-8 interacts directly with the BCR ( Table S1 ), which was also supported by a pull-down assay showing that Galectin-8 binds to the BCR. Analogously, Galectin-9 was recently shown to interact directly with the BCR and CD45 and to suppress BCR downstream signaling by restricting the lateral mobility of the receptor and favoring its association with inhibitory molecules ( Cao et al., 2018 ). In contrast to the effect of Galectin-9, we did not observe an inhibition of BCR signaling in the presence of Galectin-8.…”
Section: Discussionmentioning
confidence: 99%
“…Extracellular Galectin-9 has been implicated in inhibiting T cell immunity by promoting T cell apoptosis and differentiation into regulatory T cells (Anderson et al, 2007;Bi et al, 2008;Zhu et al, 2005). Furthermore, extracellular Galectin-9 acts as a suppressor of B cell signalling via binding to the B cell receptor (Cao et al, 2018;Giovannone et al, 2018). While these studies indicate that Galectin-9 plays an inhibitory role on lymphocytes, its function in myeloid cells remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…CD22 function as inhibitor of BCR signaling is hampered by removing five of its 12 glycosylation sites (Wasim et al, 2019). These glycans on CD22 may be bound by Galectin-9 and crosslinked with the BCR, thus explaining the inhibitory function of CD22 and Galectin-9 on BCR signaling (Cao et al, 2018;Wasim et al, 2019). Labeling specific glycan structures for microscopy or flow cytometry.…”
Section: Immune Signalingmentioning
confidence: 99%